Kesejahteraan Ibu dan Anak dalam Undang-Undang Nomor 4 Tahun 2024: Studi Kepustakaan Hukum Keluarga Islam - Anna Berliana; Muhammad Zaki; Muhammad Yasir Fauzi (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
The enactment of Law Number 4 of 2024 on Maternal and Child Welfare during the First Thousand Days of Life reflects Indonesia’s legal commitment to strengthening maternal protection, child rights, family resilience, and human resource development, yet persistent issues such as stunting, family vulnerability, limited legal literacy, and unequal access to services indicate an implementation gap between legal norms and social realities. This study aimed to analyze the implementation of Law Number 4 of 2024 and its relevance to Islamic family law in the context of Muslim families in Way Kanan Regency. This study employed a normative legal research design with a qualitative approach through library research. Primary legal materials consisted of Law Number 4 of 2024, the Marriage Law, and the Compilation of Islamic Law, while secondary materials included scholarly articles, books, government reports, and previous studies related to maternal and child welfare, Islamic family law, and maqashid sharia. The data were examined using normative content analysis and conceptual analysis to identify legal substance, Islamic family law principles, and points of harmonization between positive law and Islamic legal norms. The findings indicate that Law Number 4 of 2024 is substantively aligned with Islamic family law in the protection of mothers, fulfillment of child rights, family maintenance, hadhanah, and maqashid sharia, particularly hifz al-nafs, hifz al-nasl, and hifz al-‘aql. However, its implementation requires stronger coordination among local government, religious institutions, health workers, communities, and families, especially in addressing stunting, limited legal literacy, service inequality, and family vulnerability. This study concludes that Law Number 4 of 2024 can function as a bridge between national legal policy and Islamic family law, with implications for strengthening integrated, family-based, and religiously grounded protection for mothers and children.